Specific molecules are found to be increased in people with alopecia areata, and may be associated with an individual's level of depression. (1st January 2020) - Bain, K.A.; McDonald, E.; Moffat, F.; Tutino, M.; Castelino, M.; Barton, A.; Cavanagh, J.; Ijaz, U.Z.; Siebert, S.; McInnes, I.B.; Astrand, A.; Holmes, S.; et al.
Summary: Alopecia areata (AA) is a common disease that causes hair loss. Approximately 2% of the population are affected by AA at least once in their lifetime. The disease usually begins as a patch of hair loss on the scalp, but it can develop to affect the entire scalp or body. The hair loss is caused by cells of the immune system attacking the structures in the skin that grow hair. Unfortunately, 60% of people with AA will also develop depression, anxiety or a related condition. This study, from Scotland, aimed to find out if people with AA have different levels of molecules made by the immune system in their blood. The authors found that patients, compared to people without AA, had increased levels of multiple molecules that are produced by activated immune cells. This study also tried to understand if these molecules in blood could be contributing to the depression that some patients suffer from. This idea was based on studies in other diseases, such as rheumatoid arthritis, that have found links between molecules produced by immune cells and depression. The researchers asked patients to complete a questionnaire about their mental health to generate a depression score. Using complex equations, the authors found that two specific molecules that are increased in people with AA are associated with how depressed a patient is. The authors believe that these findings will help to understand what causes AA, and importantly may help to develop better treatments in the future. This summary relates to the study: Alopecia areata is characterized by dysregulation in systemic type 17 and type 2 cytokines, which may contribute to disease‐associated psychological morbidity